THE INFLUENCE OF MARKET ORIENTATION, TOTAL QUALITY MANAGEMENT AND ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE IN THE AUTOMOTIVE MODIFICATION SECTOR - Yohanes, Bryan Raffello; Soelaiman, Lydiawati (Graduate Program of Universitas Tarumanagara, 2023)
The development of the automotive modification industry is growing along with the development of the motor vehicle industry. Despite being hit by the Covid-19 pandemic, businesses in the automotive modification sector can still survive and are predicted to be a business sector with positive prospects. The purpose of this research is to examine the impact of market orientation, total quality management, and entrepreneurial orientation on business performance. The sample selection technique in this study used non-probability sampling techniques with purposive sampling and snowball sampling methods. The sample obtained in the study was 80 automotive modification business owners in the Jabodetabek area. The SEM-PLS method was used to analyze the data. The results showed a positive and significant influence on market orientation and entrepreneurial orientation on business performance. But total quality management has no significant effect on business performance.